2016
DOI: 10.3329/ijarit.v6i1.29211
|View full text |Cite
|
Sign up to set email alerts
|

The role of short rotation coppice technology in fuelwood supply in Rungwe district, Tanzania

Abstract: The roles of Short Rotation Coppice (SRC) Technology in fuelwood supply and offsetting CO2 emissions in the Tanzania and most African countries remain poorly understood. This study was carried in Rungwe District, Mbeya region in Tanzania, to determine trends, extent and drivers of adoption of SRC; identify various sources of household energy and assess the contribution of SRC to the total household fuelwood needs, and trees and shrub species used as sources of fuelwood. Data were collected using reconnaissance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Fecal samples were collected purposefully from thirty-six (36), adult cross-breed dairy cattle from Lushoto and Rungwe districts in Tanzania. Lushoto district lies between latitudes 4°and 6°S and longitudes 38°to 39°E in Tanga Region [22], while the Rungwe district is located in Mbeya Region and lies between latitudes 9°00 and 9°30 E and longitudes 33°E and 34°S [23]. A clean palpation sleeve and sterile lubricant was used to collect about 250 g of individual fecal samples from the rectum of each cattle and a subsample transferred into a sterile 50 ml falcon tube.…”
Section: Fecal Sample Collection Dna Extraction Librarymentioning
confidence: 99%
“…Fecal samples were collected purposefully from thirty-six (36), adult cross-breed dairy cattle from Lushoto and Rungwe districts in Tanzania. Lushoto district lies between latitudes 4°and 6°S and longitudes 38°to 39°E in Tanga Region [22], while the Rungwe district is located in Mbeya Region and lies between latitudes 9°00 and 9°30 E and longitudes 33°E and 34°S [23]. A clean palpation sleeve and sterile lubricant was used to collect about 250 g of individual fecal samples from the rectum of each cattle and a subsample transferred into a sterile 50 ml falcon tube.…”
Section: Fecal Sample Collection Dna Extraction Librarymentioning
confidence: 99%
“…Trees integrated with crop farming provide farmers with diversity of products including crops, timber, fuelwood, building poles, fruits, fodder, and medicinal plants. These products can directly be consumed for domestic uses or used for additional income generation (Karwani et al, 2016). For example, Joseph (2015) found that in the Morogoro District, crop productivity increased after implementation of agroforestry.…”
Section: The Context Of Agroforestry Systems and Farmers' Livelihoodsmentioning
confidence: 99%
“…Fecal samples were collected purposefully from thirty-six (36), adult cross-breed dairy cattle from Lushoto and Rungwe districts in Tanzania. Lushoto district lies between latitudes 4° and 6°S and longitudes 38° to 39°E in Tanga region (Mfune, 2015), while Rungwe district is located in Mbeya region and lies between latitudes 9° 00 and 9° 30 E and longitudes 33 °E and 34°S (Karwani et al, 2016). Bioinformatics and statistical analysis KRAKEN Prior to sequence analysis, filters were used to extract low-quality reads from all samples.…”
Section: Fecal Sample Collection Dna Extraction Library Constructiomentioning
confidence: 99%